AN EMPIRICAL STUDY OF GENDER DIFFERENCES IN CRIME AND JUSTICE ADMINISTRATION IN ABUJA, NIGERIA - Abdulkarim, Usman Sani (African Journal of Social and Behavioural Sciences, 2025)
This study aims to examine gender differences in crime involvement and justice administration within the Federal Capital Territory (FCT), Abuja. Using a cross-sectional survey design, data were collected from 445 respondents across the Abuja Municipal, Gwagwalada, Bwari, and Kuje Area Councils, with 434 valid responses (97.5% response rate) obtained through a multistage sampling procedure. Quantitative analysis employed descriptive statistics, Chi-square tests, Cramer’s V, mean score comparisons, and Pearson correlation analyses to assess relationships among gender, socio-economic status, and justice outcomes. Results show a significant association between gender and type of crime (χ² = 74.86, p < .001), with males predominating in violent and property offences and females in non-violent, survival-driven crimes. Socio-economic status strongly correlated with crime involvement (r = 0.69, p < .01), indicating that economic deprivation predicts higher criminal participation. Institutional bias further influenced justice outcomes, with women facing moralized judgments and men harsher sentencing for violent crimes. The study concludes that gender, poverty, and institutional practices jointly shape justice disparities in the FCT. It recommends the establishment of gender-sensitive prosecutorial guidelines as a concrete policy intervention to reduce inequities in Nigeria’s criminal justice system.